Research on batch anonymous authentication scheme for VANET based on bilinear pairing - Cheng SONG; Ming-yue ZHANG; Wei-ping PENG; Zong-pu JIA; Zhi-zhong LIU; Xi-xi YAN (Tongxin xuebao)
To solve the problem of efficiency of anonymous authentication in vehicular ad hoc network,a batch anonymous authentication scheme was proposed by using bilinear pairing on elliptic curves .The signature was generated by the roadside unit node (RSU) and the vehicle together.Thus,the burden of VANET certification center was reduced and the authentication efficiency was proved.Meanwhile,the difficulty of the attacker to extract the key was increased.Furthermore,security proofs were given to the scheme in the random oracle model.Analysis shows that the proposed scheme can meet the needs of many kinds of security requirements,the computational overhead is significantly reduced,and the authentication efficiency is improved effectively too.Therefore,the scheme has important theoretical significance and application value under computational capability constrained Internet of things (IoT) environment.